Unplugging for Student Success: Examining the Benefits of Disconnecting from Technology during COVID-19 Education for Emergency Planning - Samira Hosseini; Claudia Camacho; Katia Donjuan; Luis Pego; Jose Escamilla (MDPI AG, 2023)
The COVID-19 outbreak revealed the fragility not only of our species but also of society, which has demonstrated its ability to adapt to challenging conditions and to learn from disasters. One of the most pressing issues during the pandemic was the delivery of education during lockdowns. Education in emergency was established using various communication media, hastening the digitalization of education. However, this also highlighted the impact on the mental health of students, who were already experiencing overuse of the internet and electronic devices prior to the pandemic. In response, Tecnologico de Monterrey, a private Mexican university that also offers high school programs, launched the "Unplugged Day" initiative, which encouraged students to disconnect from electronic devices and participate in physical, cultural, creative, or reflective activities. This study applied a voluntary survey to 1850 students from March to May 2021 on a weekly basis, with the aim of analyzing symptoms of insomnia, emotions, perceptions of online education, sources of stress, and the need for professional support to manage their emotions in relation to their participation in Unplugged Day activities. Our results, obtained through a quantitative methodology, confirmed the impact of the emergency, lockdown, and forced remote education on the mental health of students. Furthermore, the results revealed that the Unplugged Day initiative is a strategy that promoted students' well-being during online education. The respondents also suggested strategies for promoting mental health and well-being of learners, whether in an emergency or not. These findings provide valuable information for governments and educational institutions to implement policies and strategies for planning education in emergency situations and for addressing the ongoing global problems of stress and mental health, which are related to the increasing use of electronic devices and the volatility, uncertainty, complexity, and ambiguity of global society. It is our responsibility to improve education so that it can play its role in preserving cultural heritage, overcoming adversity, rebuilding after catastrophes, and shaping a better future for generations to come.